Designing of Three Level 3 Phase Inverter Using Improved SPWM Modulation for different Loads - et.al, Anshu Sharma (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Many high voltage applications require three-phase inverters. The major challenge in inverter designing is the mitigation of harmonic distortion (HD) to achieve better inverting performance. Usually, sinusoidal pulse width modulation (SPWM) is widely used to trigger the inverting switches for controlling the total HD performance in the inverter. To provide the option of multiple operating ranges the multilevel inverters are designed for higher voltage operations. This paper contributes in two passes, first, an improved SPWM modulation is generated for designing the three levels inverter. Then in the second pass, the performance of the THD is evaluated under the different load conditions using V-I measurement. THD is present in the system due to the use of switches. Therefore, this paper has evaluated the performance of the proposed improved SPWM based multilevel inverter for analysis. In order to improve the performance, the modulation index of the SPWM block is varied. The performance of the component report is also presented in the short..the output waveform of the line current and the voltage are compared; The FFT analysis is done to evaluate the comparison of THD performance. It is concluded that improving the SPWM performance and the lording conditions may improve the THD performance also.